Heart failure with preserved ejection fraction: a problem of current cardiology - Saldarriaga-Giraldo, Clara (2020)
Heart failure with preserved ejection fraction (HFpEF) is a frequent and overlooked medical condition that represents a great challenge for diagnosis and treatment. Current data shows a temporal trend towards a higher prevalence of HFpEF, even above heart failure with reduced ejection frac- tion (HFrEF). The pathophysiology of HFpEF is heterogeneous and involves several factors such as genetics, lifestyle, and cardiac and non-cardiac comorbidities. These factors result in remodeling, maladaptation and cardiac stiffness, that later on cause dyspnea, exercise intolerance, and fatigue. Although the mortality outcome of HFpEF is as high as HFrEF, no speci c therapy has demonstrat- ed overall bene t in these patients; which is why future therapies will bet on an individualized approach according to the patients phenotype.